Design of high-gain wideband high directivity array antenna for satellite communication system - Jin Yuting; Xing Sirui; An Xiangdong; Wu Jian (Dianzi Jishu Yingyong, 2024)
To meet the satellite requirements for electromagnetic wave transmission in X-band communication system, a new X-band high-gain wideband high directivity microstrip array antenna is designed by selecting different antenna types. The performance of the antenna is improved by various technical means in the form of plane multilayer plates. The array antenna adopts the side fed energy input mode and the multi-layer slot coupling feed design to improve the antenna bandwidth. At the same time, the radiation layer and the feed network layer are separated to reduce the electromagnetic wave crosstalk and improve the simplicity of the separation design. The metal reflection layer is added to improve the antenna forward gain and front to back ratio. According to the project, the 64 elements and 256 elements rectangular array antenna are designed. The machining test results of two kinds antennas are basically consistent with the simulation results. The antenna achieves performance indicators such as high gain, broadband and high directivity, which is of some significance to the design of X-band satellite-earth wireless communication system.